George Bentham : Autobiography, 1800-1834 - Bentham, George, 1800-1884 (Book collections on Project MUSE., 1997)
The text of the manuscript, preserved in the Archives of the Royal Botanic Gardens, Kew, is published here for the first time, with an introduction providing historical context, explanatory notes, and indexes of plant names and of persons and works mentioned.